2009
DOI: 10.1186/1475-2875-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Field-based evidence of fast and global increase of Plasmodium falciparum drug-resistance by DNA-microarrays and PCR/RFLP in Niger

Abstract: Background: Over the last years, significant progress has been made in the comprehension of the molecular mechanism of malaria resistance to drugs. Together with in vivo tests, the molecular monitoring is now part of the survey strategy of the Plasmodium sensitivity. Currently, DNA-microarray analysis allows the simultaneous study of many single nucleotide polymorphisms (SNP) of Plasmodium isolates. In December 2005, the International Federation of the Red Cross distributed two million three hundred thousand l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Similarly, no sign of a decrease in susceptibility to LUM has been detected. This observation is consistent with earlier molecular data showing the prevalence of mutations of P. falciparum mdr1 (Pfmdr1) sequences to be low in isolates from Niger, particularly for the Y86N mutation, which is thought to confer a selective advantage on parasites, rendering them tolerant to LUM (22,27). PYD and PIP have been developed as alternative antimalarial drugs for inclusion in ART-containing combinations for the treatment of multidrug-resistant malaria.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, no sign of a decrease in susceptibility to LUM has been detected. This observation is consistent with earlier molecular data showing the prevalence of mutations of P. falciparum mdr1 (Pfmdr1) sequences to be low in isolates from Niger, particularly for the Y86N mutation, which is thought to confer a selective advantage on parasites, rendering them tolerant to LUM (22,27). PYD and PIP have been developed as alternative antimalarial drugs for inclusion in ART-containing combinations for the treatment of multidrug-resistant malaria.…”
supporting
confidence: 80%
“…This observation must be viewed in light of the results of in vivo tests conducted in Niger a decade ago, for which a treatment success rate of about 85% was reported for CQ. The trend in 2011 (11% of isolates presenting a mutated codon 76) is therefore distinctly different from those reported for molecular studies carried out between 2003 and 2007 in Niger, in which the prevalence of Pfcrt 76T was reported to be between 32.4% and 50.8% (22,32). However, given the limited number of isolates examined and the short time interval between these studies, it is too soon to draw any firm conclusions about a shift toward an improved susceptibility of parasites to CQ in Niger.…”
mentioning
confidence: 40%
“…Using a geographical database of molecular biomarkers as described elsewhere [16], we obtained prevalence esti-mates of Pfdhps 581G from 44 locations that had been measured within AE2 years of the IPTp-SP studies. There were 20 locations within <100 miles of the pregnancy study sites and 24 locations within 100-250 miles as shown in Table 5 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Effect Modification Of Pfdhps 581gmentioning
confidence: 99%
“…They also described the assay as suitable to cope with the problem of multiplicity of infections and the determination of the most dominant haplotype representing the clinical malaria-causing clone. While the present study only worked with cultured organisms, the authors and collaborators conducted further successful field studies on the basis of the microarray system using patient samples in Tanzania [176], Niger [177], Papua New Guinea [178], and the Solomon Islands [179]. In an interesting study, the group around Hans-Peter Beck used the same technological approach to genotype polymorphisms, that is, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP3A4, CYP3A5, and NAT2, which are known to have an impact on human malarial drug metabolisms [180].…”
Section: Malariamentioning
confidence: 99%